Analisis Manajemen Risiko Pembiayaan Mikro Syariah Berbasis Karakteristik Masyarakat (Studi pada Koperasi Mitra Manindo, Kabupaten Mandailing Natal, Sumatera Utara) - Nasution, Lokot Zein (Islamic Circle, 2020)
Distribution of Islamic microfinance is often constrained by the characteristics of the poor who tend to be conservative. This has implications for the difficulty of efforts to improve the welfare of the poor through increased work ethic and productivity. Various discourses propose the application of risk management based on mapping the characteristics of the poor in the distribution of micro-scale financing, including for the sharia segment. Therefore, this study aims to analyze the characteristics of the poor as the basis for risk management of Islamic micro finance. This research takes a case study on the Mitra Manindo Cooperative in Mandailing Natal Regency, North Sumatra Province. The research method was carried out by taking 102 research samples using questionnaires and analyzed through the development analysis approach. The results of the study concluded that: (i) Mitra Manindo Cooperative members have different business characteristics and performance; (ii) each member has a different level of business problems; and (iii) each member has different characteristics, especially in the work ethic. Characteristics of members in general can be categorized into four clusters, namely dynamic, active, passive, and potential. Based on these results, a cluster-based management method is needed which has implications for the urgency of financing management as a form of financing mitigation. Characteristic mapping is an effort to reduce the uncertainty (gharar) of sharia microfinance governance that emphasizes the importance of transparency, fairness, and equity. This finding can be a proliferation in constructing the mapping design of the characteristics of the poor as a single segment of microfinance.